Site accessibility tailors DNA cleavage by restriction enzymes in DNA confined monolayers. Issue 19 (28th April 2017) - Rotella, Chiara; Doni, Giovanni; Bosco, Alessandro; Castronovo, Matteo; De Vita, Alessandro; Casalis, Loredana; Pavan, Giovanni M.; Parisse, Pietro
Abstract : DNA substrate conformation strongly affects the accessibility of restriction sites, consequently hindering/favouring the enzymatic restriction reaction in a programmable way. Abstract : Density-tunable nanografted monolayers (NAMs) of short oligonucleotide sequences on gold surfaces show novel properties that make them suitable for advanced biosensing applications, and in particular to study the effects of crowding and confinement on biomolecular interactions. Here, combining atomic force microscopy nanolithography, topography measurements and coarse-grained molecular dynamics simulations, we investigated restriction enzyme reaction mechanisms within confined DNA brushes highlighting the role played by the DNA sequence conformation and restriction site position along the chain, respectively, in determining the accessibility of the enzyme, and its consequent cleavage efficiency.